f ( x , y , z ) = x 3 y cos ( y ln x ) + e x y z − ln ( z + 1 ) π
Given the above and that ∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ f ) ) = e 8 n at the point ( 2 , − 4 , 1 ) , find n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x , y , z ) ∂ x ∂ f ∂ y ∂ ( ∂ x ∂ f ) ∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ f ) ) = x 3 y cos ( y ln x ) + e x y z − ln ( z + 1 ) π = ∂ x ∂ x 3 y cos ( y ln x ) + ∂ x ∂ e x y z − 0 = ∂ y ∂ ( ∂ x ∂ x 3 y cos ( y ln x ) ) + ∂ y ∂ ( ∂ x ∂ e x y z ) = 0 + ∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ e x y z ) ) = ∂ z ∂ ( ∂ y ∂ y z e x y z ) = ∂ z ∂ ( z e x y z + x y z 2 e x y z ) = e x y z + x y z e x y z + 2 x y z e x y z + x 2 y 2 z 2 e x y z = e x y z ( 1 + 3 x y z + x 2 y 2 z 2 ) Term is independent of x . Term is independent of z .
Therefore,
∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ f ) ) ∣ ∣ ∣ ∣ ( 2 , − 4 , 1 ) = e − 8 ( 1 − 2 4 + 6 4 ) = e 8 4 1
⟹ n = 4 1
Problem Loading...
Note Loading...
Set Loading...
Notice that ∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ f ) ) will only leave terms with z , since ∂ z ∂ of all other terms with x and y will go to 0 . Also notice that ∂ x ∂ ( − ln ( z + 1 ) π ) = 0 . Thus,
∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ f ) ) = ∂ z ∂ ( ∂ y ∂ ( ∂ x ∂ ( e x y z ) ) ) = ∂ z ∂ ( ∂ y ∂ ( y z e x y z ) ) = ∂ z ∂ ( z e x y z + x y z 2 e x y z ) = e x y z ( 1 + 3 x y z + ( x y z ) 2 )
Plugging in our point ( x , y , z ) = ( 2 , − 4 , 1 ) , we have e − 8 ( 1 − 2 4 + 6 4 ) = 4 1 e − 8 , so our answer is 4 1 .